2009
DOI: 10.14430/arctic358
|View full text |Cite
|
Sign up to set email alerts
|

A Near-Total Decline in Caribou on Prince of Wales, Somerset, and Russell Islands, Canadian Arctic

Abstract: ABSTRACT. The number of caribou (Rangifer tarandus) on Prince of Wales, Somerset, and Russell islands in the south-central Canadian Arctic declined by 98% in 15 years, from an estimated 6048 (16% calves) in 1980 to an estimated 100 (0% calves) in 1995. Those estimates were obtained by systematic aerial surveys that used the same design and methods and comparable survey coverage. We do not have the data needed to determine the rate of decrease between 1980 and 1995 or its possible causes. There is no evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…Only a handful of "Peary-like" caribou were reported on the island in 1989, and Inuit hunters recognized both Pearylike and barren-ground caribou coming from the Boothia Peninsula and the mainland (Miller, 1991). If Peary caribou formerly migrated between PWI and KWI, the crash of the PWI Peary population in the mid-1990s (Miller and Gunn, 2003;Gunn et al, 2006) has reduced the likelihood of Peary caribou on KWI more recently (A. Gunn, pers.…”
Section: Peary Caribou On Kwimentioning
confidence: 99%
See 1 more Smart Citation
“…Only a handful of "Peary-like" caribou were reported on the island in 1989, and Inuit hunters recognized both Pearylike and barren-ground caribou coming from the Boothia Peninsula and the mainland (Miller, 1991). If Peary caribou formerly migrated between PWI and KWI, the crash of the PWI Peary population in the mid-1990s (Miller and Gunn, 2003;Gunn et al, 2006) has reduced the likelihood of Peary caribou on KWI more recently (A. Gunn, pers.…”
Section: Peary Caribou On Kwimentioning
confidence: 99%
“…Hunters have noted increasing numbers of caribou wintering near Gunn and Ashevak, 1990:1), and a population of Peary caribou is also known to calve on the Boothia Peninsula (COSEWIC, 2011). Although there is common movement between PWI, Somerset Island, and the Boothia Peninsula (Gunn and Ashevak, 1990;Gunn et al, 2006;McFarlane et al, 2009;Jenkins et al, 2011;McFarlane et al, 2014), there is no mention in the literature of potential east-west migrations from the Boothia Peninsula to KWI.…”
Section: Peary Caribou On Kwimentioning
confidence: 99%
“…erefore, for the purposes of conservation and management we consider those caribou to constitute one geographic caribou population ( Fig. 1: Miller et al, 2005;Gunn et al, 2006;Miller et al, 2007b). is population will hereafter be referred to as the Prince of Wales Island-Somerset Island-Boothia Peninsula Complex (PSBC) caribou population.…”
Section: Study Populationmentioning
confidence: 99%
“…e PSBC caribou population declined from about an estimated 6000 in 1980 (Gunn & Miller, 1983) to no more than several dozen caribou in the mid 1990s (Miller, 1997;Gunn & Dragon, 1998;Gunn et al, 2006;Miller et al, 2007a). A remnant population remains, but there is no evidence of a documented major recovery since then.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…In 2004, a combination aerial and ground survey of caribou by the Nunavut Wildlife Service, using a helicopter and snowmobile-mounted Inuit observers, failed to find even one caribou or any recent sign of caribou on Prince of Wales and Somerset islands (Gunn et al, 2006). Gunn et al (2006) found no evidence that an absolute shortage of forage, relative unavailability of forage due to extreme snow and ice conditions, intraspecific competition with muskoxen (Ovibos moschatus), large-scale emigration, The Eleventh North American Caribou Workshop, Jasper, Alberta, Canada, 24-27 April, 2006. widespread disease, or heavy parasite burdens played a major role in the near-total loss of caribou on Prince of Wales, Russell, and Somerset islands. They did, however, conclude that both wolf (Canis lupus) predation and hunting on Prince of Wales, Russell, and Somerset islands most likely contributed to and deepened the final stage of the decline.…”
mentioning
confidence: 99%